Case report and literature review: exploration of molecular therapeutic targets in recurrent malignant meningioma through comprehensive genetic analysis with Todai OncoPanel - Ohara, Kenta; Miyawaki, Satoru; Nakatomi, Hirofumi; Okano, Atsushi; Teranishi, Yu; Shinya, Yuki; Ishigami, Daiichiro; Hongo, Hiroki; Takayanagi, Shunsaku; Tanaka, Shota; Shinozaki-Ushiku, Aya; Kohsaka, Shinji; et al. (Frontiers in Neurology, 2023)
Background Despite accumulating research on the molecular characteristics of meningiomas, no definitive molecularly targeted therapy for these tumors has been established to date. Molecular mechanisms underlying meningioma progression also remain unclear. Comprehensive genetic testing approaches can reveal actionable gene aberrations in meningiomas. However, there is still limited information on whether profiling the molecular status of subsequent recurrent meningiomas could influence the choice of molecular-targeted therapies. Case presentation We report a case of meningioma with malignant progression and multiple recurrences. We performed matched tumor pair analysis using the Todai OncoPanel to investigate the possibility of additional standard treatments. The loss of several chromosomal regions, including NF2 and CDKN2A, which is associated with aggressive meningiomas, was considered a significant driver event for malignant progression. Using additional matched tumor pair analysis, mutations in TRAF7, ARID1A, and ERBB3 were identified as subclonal driver events at the time of recurrence. No genetic aberrations were found for which evidence-based targeted therapy was applicable. We also reviewed previous reports of molecular therapies in meningioma to discuss issues with the current molecular testing approach. Conclusion Gene panel testing platforms such as the Todai OncoPanel represent a powerful approach to elucidate actionable genetic alterations in various types of tumors, although their use is still limited to the diagnosis and prediction of prognosis in meningiomas. To enable targeted molecular therapy informed by gene-panel testing, further studies including matched tumor pair analyses are required to understand the molecular characteristics of meningiomas and develop treatments based on genetic abnormalities.